The Uterus Flag Project - Terrilynn; Anonymous
Stitchers, knitters, fabric artists and creative people Those concerned with social justice. This is a collaborative, social practice art project where women and men use some form of fiber arts and stitch on a pre-painted, piece of fabric 7" x 9" inches tall and write a reflection statement about their thoughts concerning women's health issues. terrilynnquick@gmail.com http://uterusflagproject.blogspot.com/ http://www.facebook.com/UterusFlagProject The Project The Uterus Flag Project is a profound body of work that allows me to share my creativity and my social concerns rooted in the medicalization of women. The project has evolved into sharing and creating awareness about the importance of the organ, the uterus. The participants become the artists and when the project is exhibited it takes on a feeling of synergism focused on women's health. My mission is educating through the power of art, integrating the ideals of feminism to change the consciousness about women's health. My personal concerns began with discovering I had an unnecessary hysterectomy. Through this project, I have heard the voices of other women, their personal stories and concerns about their health. It is my belief that women deserve access to valid information to help them make better medical choices.